1946
DOI: 10.1021/ja01212a504
|View full text |Cite
|
Sign up to set email alerts
|

Some Substituted Acetophenones1

Abstract: II (2 g.) was dissolved in acetic acid (50 cc.) and, after addition of potassium dichromate (2 g.) in acetic acid (30 cc.), heated to boiling for two minutes. Upon pouring onto ice, a yellow precipitate (1.7 g.) was obtained. It crystallized from ethanol in yellow prisms of m. p. 135-136°. An additional recrystallization from acetic acid raised the m. p. to 140-141 °, as reported in the literature.6 The yield of pure produpt was 1.2 g. (60%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These authors suggested for the first time" 1 the name sulfine for thiocarbonyl S-oxides to indicate the structural relationship with sulfenes, which are thiocarbonyl S,Sdioxides' 11 . In the same year the first thioaldehyde 5-oxide 4 was Downloaded by [McMaster University] at 10:58 03 December 2014 prepared by Strating, Thijs and Zwanenburg" 0 ' also employing the dehydrochlorination method.…”
Section: Chartmentioning
confidence: 99%
“…These authors suggested for the first time" 1 the name sulfine for thiocarbonyl S-oxides to indicate the structural relationship with sulfenes, which are thiocarbonyl S,Sdioxides' 11 . In the same year the first thioaldehyde 5-oxide 4 was Downloaded by [McMaster University] at 10:58 03 December 2014 prepared by Strating, Thijs and Zwanenburg" 0 ' also employing the dehydrochlorination method.…”
Section: Chartmentioning
confidence: 99%
“…As determined by internal standard, the best yield for iodobenzene 5 (88%) was obtained from a reaction of 2a with three equivalents of potassium iodide at 50 °C (entry 2) . Purification of the crude product by column chromatography confirmed this result and led to an identical yield of 88%, which corresponds to 2.09 g on the 10 mmol reaction scale.…”
Section: Resultsmentioning
confidence: 99%
“…imines 1 and 5). aid of prochiral N-alkyl probes (e.g., 14), since such compounds possess a molecular a plane that passes through the N-R moiety in the bisected conformation depicted in 14; hence, the paired geminal substituents in the N-R group are enantiotopic and isochronous.4 However, if R is chiral (e.g., 15) the o-methyl groups (and the m-hydrogen atoms) will be 1.29 (3 H, d, Vhch = 6.4 Hz, CHCH3), 1.59 (3 H, s, 0-CH3), 2.11 (3 H, s, =CCH3), 2.17 and 2.24 (each 3 H, s, 0-CH3' and p-CH3>, 3.98 (1 H, q, VHcch = 6.4 Hz, NCH), 6.68 (1 H, s, meta H), 6.78 (1 H, s, meta H'), and 7.11 (5 H, br s, CeHs). The =CCD3 analogue of 15 (prepared by deuterium exchange with CD3OD) showed the same chemical shifts in CCI4 solution, except that the signal at b 2.11 had disappeared, thus confirming the assignment of this signal to the =CCH3 group.…”
Section: Resultsmentioning
confidence: 99%